KOHESI GRAMATIKAL DALAM TEKS LAPORAN PENELITIAN DOSEN FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SEMARANG - Pristiwati, Rahayu (Jurnal Penelitian Pendidikan, 2011)
The purpose of this study is to prove the existence of grammatical cohesion in the research report text of the lectures of Faculty of Languages and Arts, Semarang State University and to identify the various devices used in the text of the research report, from the lecturer of Faculty of Languages and Arts, Semarang State University. The research was conducted with qualitative and descriptive approach. The source of research data is the lecturerâs text of the research report that there are seven research report. Research data in the form of text snippets of the Semarang State Universityâs lecurerâs research report that allegedly contain grammatical cohesion. The findings of this study is the presence of grammatical cohesion in the Faculty of Language and Art Semarang State University âlecturerâs text of the research report on the use of words or phrases. Grammatical cohesion devices in the Faculty of Language and Art Semarang State University âlectureâs text research report, which covers (1) reference (reference), (2) substitution, (3) ellipsis, and (4) conjunction. Based on these findings, it can be put forward suggestions that language users should be able to make use of grammatical cohesion in an effort to speak effectively and efficiently, both verbal and written. Excavations of various grammatical cohesion devices in the Faculty of Language and Art Semarang State University âlectureâs text research report should continue to be given the possibility of using other devices than those found in this study.